2009
DOI: 10.1016/j.peva.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

On the optimality of field-line routing in massively dense wireless multi-hop networks

Abstract: A B S T R A C TWe consider the load balancing problem in large wireless multi-hop networks by applying the continuum approximation. The task is to find routes, geometric curves, such that the maximal traffic load in the network is minimized. In finite fixed networks, multi-path routes generally yield a lower congestion and thus allow higher throughput. In contrast, we show that in dense wireless multi-hop networks, the optimal load balancing can be achieved by a destination based single-path routing referred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…The forwarding load appears to correspond to the scalar sum of traffic flows of different classes. This means that the optimal solution (with respect to this objective) can be achieved by single path routes, a result obtained also in [15]. Similar problems have been also studied in [8], as well as in works doing load balancing by analogies to Electrostatics (see e.g.…”
Section: Introductionmentioning
confidence: 79%
“…The forwarding load appears to correspond to the scalar sum of traffic flows of different classes. This means that the optimal solution (with respect to this objective) can be achieved by single path routes, a result obtained also in [15]. Similar problems have been also studied in [8], as well as in works doing load balancing by analogies to Electrostatics (see e.g.…”
Section: Introductionmentioning
confidence: 79%
“…They further showed that, in the limit of massively-dense networks, multiple-path routing for optimal load balancing can be achieved by using single-path routing [Hyytiä and Virtamo 2007a]. In addition, such a single-path routing depends on destination but not source and thus may be represented as a routing field [Hyytiä and Virtamo 2009]. Altman et al [2008] examined the routing problem of massively-dense networks in the context of road traffic engineering.…”
Section: Related Workmentioning
confidence: 99%
“…In order to analyze the floating content concept, it is important to characterize the movement, e.g., how often a node crosses a given line segment. To this end, let ϕ(r, φ) denote the so-called angular node flux at r in direction φ, which is defined as the rate of nodes moving in direction (φ, φ+dφ) across a small perpendicular line segment of ds divided by ds · dφ at the limit ds, dφ → 0 [13], [15], as illustrated in Fig. 2.…”
Section: Preliminaries a Fluxes And Stationary Distributionmentioning
confidence: 99%
“…We develop models for analyzing the feasibility of the floating content concept by using spatial modeling techniques adopted from physics [13], similarly as have been used for modeling the capacity of so-called dense wireless multihop networks, see, e.g., [14], [15]. The fundamental objective is to establish the criticality condition for the system, i.e., an explicit relation which determines when the information remains available within the anchor zone infinitely long at the fluid limit (large population).…”
Section: Introductionmentioning
confidence: 99%